Imagens de violência como fetiche no contexto escolar - Coelho, Hélida Costa (2019)
This research explores interpretative possibilities and learning developed from images of violence in the school context. Increasing physical, psychological and symbolic conflicts involving students and teachers interfere and compromise pedagogical and learning processes, emphasizing the need to problematize and discuss violence in formal and non-formal educational environments. The theoretical references of this research are anchored in the poststructuralist perspective, in dialogue with the principles of the education of visual culture. Of a qualitative character, the approach that bases the methodological procedures used in the field work has as an emphasis, a critical analysis of the school reality. The field research was done at the State School named Deusolina Salles Farias, in the city of Macapá/AP, and the data was produced through individual interviews and the creation of a focus group with eight students from Elementary School II, with four men and four women. Visual narratives produced by the participants in the research contributed to the production of meaningful data that put objective and subjective aspects of everyday school practice into the perspective. The results of the investigation point to students’ interest in questioning, discussing and reflecting on ways of understanding the problem and implementing alternative manners of talking to the world, to the ‘other’ and to the school environment.